1999
DOI: 10.1001/archopht.117.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of βig-h3 Protein in 5q31-Linked Corneal Dystrophies and Normal Corneas

Abstract: To characterize the relation of the ␤ig-h3 protein to the diagnostic corneal deposits in the hereditary corneal dystrophies recently shown to have mutations in the βig-h3 gene on chromosome 5q31. Methods: Corneas with lattice, granular, mixed granularlattice ("Avellino"), and 2 types of Reis-Bü cklers dystrophy were diagnosed by the histochemical and ultrastructural characteristics of their abnormal aggregates. Dystrophic and normal corneas were compared for immunolocalization of ␤ig-h3 protein. Results: In no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 24 publications
(43 reference statements)
5
48
0
2
Order By: Relevance
“…43 It appears that mutant βig-h3 protein self-polymerizes and/or incorrectly binds to other corneal components resulting in the abnormal deposits found in these dystrophies. 44 Hereditary hemorrhagic telangiectasia (HHT) type 1 or OslerWeber-Rendu disease is caused by mutations of endoglin. 10 In HHT type II, mutations of activin receptor-like kinase 1 (ALK1) have been identified.…”
Section: Tgf-β and Diseasementioning
confidence: 99%
“…43 It appears that mutant βig-h3 protein self-polymerizes and/or incorrectly binds to other corneal components resulting in the abnormal deposits found in these dystrophies. 44 Hereditary hemorrhagic telangiectasia (HHT) type 1 or OslerWeber-Rendu disease is caused by mutations of endoglin. 10 In HHT type II, mutations of activin receptor-like kinase 1 (ALK1) have been identified.…”
Section: Tgf-β and Diseasementioning
confidence: 99%
“…15,20,21 Immunohistochemical studies demonstrated that the mutated keratoepithelin is a major component of the corneal deposits. [20][21][22] The keratoepithelin protein has four internal repeat domains and most of the mutations reported are located in the amino acid R124 or in the fourth fascilin-like domain.…”
Section: Discussionmentioning
confidence: 99%
“…The transforming growth factor beta induced gene (TGFBI) on chromosome 5, responsible for the quality and quantity of keratoepithelin, has been related to several corneal dystrophies. The immunoreactivity of the keratoepithelin protein has been demonstrated in the dystrophic deposits of corneas with granular, Avellino, Reis-Buckler, lattice and Thiel-Behnke dystrophies, all related to the TGFBI gene suggesting that keratoepithelin is a major component of these deposits (1,7) . It has also been shown that the deposits contain keratoepithelin, together with nonkeratoepithelin proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The inference is that mutated keratoepithelins, diffusing predominantly from the epithelium, coaggregate with an assortment of other proteins over a long period of time to form the deposits characteristic of the disorder (8) . Several substances reported to date include vimentin, immunoglobulin κ and λ light chains, microfibrillar protein lectinpositive carbohydrate, amyloid P protein, phospholipids, and epithelial proteins, such as the cytokeratins (3,(7)(8)(9) (Figure 1). Cytokeratins (CKs) are water-soluble proteins found in most celltypes having characteristics of epithelial cells (10) .…”
Section: Introductionmentioning
confidence: 99%